IMPLEMENTASI PERATURAN WALIKOTA SAMARINDA NOMOR 43 TAHUN 2020 TENTANG PENERAPAN DISIPLIN DAN PENEGAKAN HUKUM PROTOKOL KESEHATAN SEBAGAI UPAYA PENCEGAHAN DAN PENGENDALIAN CORONA VIRUS DISEASE 2019 (COVID-19) MENGENAI PENGGUNAAN MASKER DI KOTA SAMARINDA - Oey Vonny Winata (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACK This extraordinary incident originated from a case of pneumonia caused by a virus from the Corona Virus extended family, but this virus has never been known before so it is referred to as a new type of Corona or Novel Coronavirus.This research is empirical juridical research. Empirical legal research is a legal research method that functions to be able to see the life of the law in a real sense and to examine how the law works in a society.Masks are used to avoid exposure to the Corona Virus that is hitting Indonesia, including Samarinda City so that the number of people exposed to this virus can be reduced. Mayor Regulation Number 43 of 2020 regarding health protocols including the use of masks was socialized by the Samarinda City Covid-19 Handling Task Force through word of mouth, social media, seminars, through printed media such as distributing pamphlets, banners and creating a Covid-19 Handling Task Force team at the sub-district, sub-district, to the RT / RW levelThere are 5 factors that influence law enforcement. However, the factors of the community that make the implementation of Mayor Regulation Number 43 of 2020 are hampered because there are still people who do not use masks. This is proven by the fact that people feel lazy to use masks when traveling to nearby places and wearing masks can hinder the activities of the community itself. This is what causes the people of Samarinda City to still not wear masks. Keywords   :   Implementation of Samarinda Mayor Regulation. Health    Protocol for the Use of Masks